Methodology for exploring, documenting, and improving humanitarian service learning in the university - Berg, Devin R., 1986-; Buchanan, Elizabeth A., 1968-; Lee, Tina, 1976- (My University, 2016)
Through the use of service learning in higher education, universities hope to both provide real benefit to the partnering community and allow students to develop a greater understanding of course curriculum, their discipline, and their personal positioning within society. Through these educational activities, service learning seeks to engage students in critical thinking processes while simultaneously achieving a greater sense of civic and social responsibility through targeted participation in meaningful community service activities. However, in practice, service learning can take a variety of forms predicated on technical, cultural, societal, and political constraints. Thus, while some work shows positive effects on students? attitudes, social behaviour, and academic performance, less research has demonstrated long-term community impact. Nor has much research shown that participation in service learning has a long-term impact on students' ethical perspectives and frameworks, and whether those ethical frames carry on to their professional careers. Moreover, as institutions partner with such humanitarian service groups as Engineers Without Borders USA, we know considerably less about the institutional cultures and climates that are developed through such partnerships and how sustainable they are, given those inherent technical, political and cultural limitations. As a first step towards these goals, this paper proposes a methodology for investigating the impacts of service learning activities on both the students and communities involved.
Includes bibliographical references.
Keywords: engineering education; higher education; humanitarian; humanitarian engineering; Engineering ethics; Professional ethics; Engineering; Service learning; Engineering--Study and teaching; Education, Higher; Curriculum planning; Inquiry (Theory of knowledge)